Estimation methods of theree parameters discrete generalized exponential distribution - M. Shuaib Khan; M. Aleem; Muhammad Akbar Ali Shah (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2010)
This article presents the estimation methods of three parameters Discrete Generalized Exponential distribution. The two-parameter generalized exponential distribution was introduced by Gupta and Kundu (1999). We present the three parameters discrete Generalized Exponential distribution is the sum of infinite probability function. Moment estimation, inverse integer moment estimation, moment generating function, maximum likelihood estimation and L-moment estimation are derived for this infinite probability function.
Keywords: 330; Three parameter Generalized Exponential distribution; Sum of infiniteprobability function; Moment estimation; moment generating function; maximum likelihood estimation and L-moment estimation